MENEJEMEN PENINGKATAN MUTU PEMBELAJARAN KITAB KUNING - M. Abdul Ghofur (INAIFAS PRESS, 2020)
This study aims to determine the quality management and effectiveness of learning the yellow book at Al Bidayah Jember Islamic Boarding School, because with good management it will produce good learning as well. This research uses descriptive method with a qualitative approach. The subjects of the study were the clerics, administrators and several students. The results of this study indicate that management in the learning of the yellow book is very important, which includes the rules of the Islamic boarding school, teaching methods, teaching strategies, and many others that researchers cannot mention one by one.